Modelos para predecir las distancias de dispersión de semillas por micos churucos (Lagothrix Lagothricha): aportes de estudios en campo y en cautiverio - Stevenson, Pablo R.; Departamento de Ciencias Biológicas Universidad de Los Andes Bogotá, Colombia (2003)
It is very difficult to measure the seed shadows generated by animal vectors, especially when they are very mobile, but the knowledge of these seed shadows is essential to understand plant demographic processes. For this reason several authors have tried to use different methods to estimate seed shadows, using parameters such as passage rates through the gut and some approximation to asses ranging behavior. In some cases data on passage rates can be obtained from captive animals. Information from captive woolly monkeys with field data was combined, in order to generate models to predict straight dispersal distance, and also to assess the influence ofseed size and diet type on passage rates. Small plastic beads and large seeds were added to the food of four animals at the “Jaime Duque” Zoological Park, near Bogotá, which were recovered afterwards to  estimate passage rates. Longer retention times were found for small  “seeds” than for larger seeds, and in general shorter retention times were associated with a diet based on fruits, in contrast to a more fibrous diet. Passage rates in captivity were about twice as long as those in the field.  Finally, eight models to predict dispersal distance from information on passage rates and ranging patterns were formulated, combining data from the captive study and data from the field (CIEM, Tinigua Park, Colombia). The models that best fit the empirical data were those that include the distribution of distances from the field ranging patterns, while the models assuming linear progression of the animals did not fit the observed patterns. Passage rate seems to be a parameter of secondary importance to predict seed dispersal distance for our study population.